Green Synthetic Transformations Using Ionic Liquid, Solid-Phase Supports and Electricity - Swaroop , Toreshettahally R.; Rangappa, Kanchugarakoppal S. (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
We present green synthetic transformations in this chapter. Synthesis of 4H-chromenes and pyranopyrazoles in choline chloride-urea ionic liquid, solid phase synthesis of \(α\)-oxoketene-N,S-acetals, \(β\)-enaminones and 4-quinolones, and electrochemical synthesis of thiosulfonates and phosphonates is detailed. Besides, we also present electrochemical reductive coupling of o-substituted carbonyl compounds and m-substituted carbonyl compounds. We have given possible mechanisms for the formation of each product.